2017
DOI: 10.1080/2162402x.2017.1338230
|View full text |Cite
|
Sign up to set email alerts
|

CD103+ tumor-infiltrating lymphocytes are tumor-reactive intraepithelial CD8+ T cells associated with prognostic benefit and therapy response in cervical cancer

Abstract: Human papilloma virus (HPV)-induced cervical cancer constitutively expresses viral E6/E7 oncoproteins and is an excellent target for T cell-based immunotherapy. However, not all tumor-infiltrating T cells confer equal benefit to patients, with epithelial T cells being superior to stromal T cells.To assess whether the epithelial T cell biomarker CD103 could specifically discriminate the beneficial antitumor T cells, association of CD103 with clinicopathological variables and outcome was analyzed in the TCGA cer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
104
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 128 publications
(120 citation statements)
references
References 52 publications
9
104
1
1
Order By: Relevance
“…Indeed, NKG2A expression was recently also reported on T cells from normal lung tissues, where they were poised for rapid responsiveness (Hombrink et al, 2016). In combination with the fact that CD103 + T cells have been associated with good clinical prognosis in multiple cancers (Webb et al, 2014b, Komdeur et al, 2017, Wang et al, 2016, Bosmuller et al, 2016, Webb et al, 2014a), these findings portrays the NKG2A-positive CD8 T cell subset as tissue-residing lymphocytes with immediate effector functions kept in check by their inhibiting receptors, such as NKG2A.…”
Section: Discussionmentioning
confidence: 91%
“…Indeed, NKG2A expression was recently also reported on T cells from normal lung tissues, where they were poised for rapid responsiveness (Hombrink et al, 2016). In combination with the fact that CD103 + T cells have been associated with good clinical prognosis in multiple cancers (Webb et al, 2014b, Komdeur et al, 2017, Wang et al, 2016, Bosmuller et al, 2016, Webb et al, 2014a), these findings portrays the NKG2A-positive CD8 T cell subset as tissue-residing lymphocytes with immediate effector functions kept in check by their inhibiting receptors, such as NKG2A.…”
Section: Discussionmentioning
confidence: 91%
“…Tumor‐associated human CD8 + T cells with a CD69 + CD103 + T RM phenotype have been described in patients suffering from a broad variety of cancers, including urothelial, colorectal, ovarian, endometrial, cervical and lung cancer, as well as glioblastoma and melanoma . Often these cells are confined to epithelial compartments within or around tumors and their transcriptional profile resembles that of T RM cells in murine tissues, meaning that tumor‐associated CD8 + CD69 + CD103 + T cells are likely bona fide T RM cells . Intriguingly, strong accumulation of these T RM cells or their transcriptional marks, respectively, correlates with prolonged survival in a spectrum of patients and has been shown to be a better prognostic marker than total CD8 + T cell counts in some cancers .…”
Section: Role Of Trm Cells In Cancer Immune Surveillancementioning
confidence: 99%
“…Reports have demonstrated that a high number of tumour‐infiltrating T RM cells is linked to improved prognosis in patients with urinary bladder, lung, cervical and ovarian cancers [7, 8, 9, 10]. The improved prognosis is due to the capacity of T RM cells to produce IFN‐γ upon in‐situ antigen recognition [11], resulting in the recruitment of circulating T cells from the blood [12].…”
Section: Introductionmentioning
confidence: 99%